2019
DOI: 10.1186/s12909-019-1687-7
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring burnout and the association with the educational climate in pediatric residents in Thailand

Abstract: Background This study, undertaken in Bangkok, Thailand, explored the extent to which paediatric residents in a non-Western setting experienced burnout and the potential association with factors in the medical educational climate and work-related quality of life. Methods An exploratory sequential mixed methods design was employed in a cross-sectional study. The initial, quantitative phase used the validated Maslach Burnout Inventory, the Postgraduate Hospital Educational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 26 publications
1
33
0
6
Order By: Relevance
“…De acuerdo a un metaanálisis la prevalencia general del Burnout en residentes de todas las especialidades médicas, fue de 37,5% y en los residentes de pediatría en (9) particular fue del 30% . Puranitee y cols, no encontraron Burnout en un grupo de 51 residentes de Pediatría en Tailandia, mientras que en Arabia Saudita, Hameed y cols, encontraron 81% de casos de Burnout en 181 residentes de todas las (10,11) especialidades .…”
Section: Discussionunclassified
“…De acuerdo a un metaanálisis la prevalencia general del Burnout en residentes de todas las especialidades médicas, fue de 37,5% y en los residentes de pediatría en (9) particular fue del 30% . Puranitee y cols, no encontraron Burnout en un grupo de 51 residentes de Pediatría en Tailandia, mientras que en Arabia Saudita, Hameed y cols, encontraron 81% de casos de Burnout en 181 residentes de todas las (10,11) especialidades .…”
Section: Discussionunclassified
“…Another research emphasized the effect of stressful on-call duties, and long duty hours on the increase in the incidence of burnout [5]. In addition, a study suggested minimizing work hours and assigning health care workers to speci c rules in order to prevent physician burnout [16]. Moreover, a survey advised a time off to improve residents' well-being as it showed that long duty hours could cause residents burnout which can cause depression, substance abuse, and suicide attempt [2][3]5].…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Papers included in this narrative review used different instruments to measure the educational environment and burnout. [47][48][49][50][51][52] van Vendeloo et al 47 performed a national Dutch crosssectional online survey in 2015. They used the Scan of Postgraduate Educational Environment Domains (SPEED) to measure the learning environment on content, organization and atmosphere, and the Dutch version of the Maslach Burnout Inventory (UBOS-C) to measure burnout.…”
Section: Provision Of Servicementioning
confidence: 99%